Prospects for strain-specific immunotherapy in Alzheimer’s disease and tauopathies - Bittar, Alice (NPJ Vaccines, 2018)
With increasing age, as the incidence of Alzheimer’s disease is increasing, finding a therapeutic intervention is becoming critically important to either prevent or slow down the progression of the disease. Passive immunotherapy has been demonstrated as a successful way of reducing large aggregates and improving cognition in animal models of both tauopathies and Alzheimer’s disease. However, with all the continuous attempts and significant success of immunotherapy in preclinical studies, finding a successful clinical therapy has been a great challenge, possibly indicating a lack of accuracy in targeting the toxic species. Both active and passive immunotherapy approaches in transgenic animals have been demonstrated to have pros and cons. Passive immunotherapy has been favored and many mechanisms have been shown to clear toxic amyloid and tau aggregates and improve memory. These mechanisms may differ depending on the antibodie's' target and administration route. In this regard, deciding on affinity vs. specificity of the antibodies plays a significant role in terms of avoiding the clearance of the physiological forms of the targeted proteins and reducing adverse side effects. In addition, knowing that a single protein can exist in different conformational states, termed as strains, with varying degrees of neurotoxicity and seeding properties, presents an additional level of complexity. Therefore, immunotherapy targeting specifically the toxic strains will aid in developing potential strategies for intervention. Moreover, an approach of combinatorial immunotherapies against different amyloidogenic proteins, at distinct levels of the disease progression, might offer an effective therapy in many neurodegenerative diseases.